Charlie and the great glass elevator - Dahl, Roald; Blake, Quentin, ill. (New York : Scholastic, 1998)
Taking up where Charlie and the Chocolate Factory leaves off, Charlie, his family, and Mr. Wonka find themselves launched into space in the great glass elevator.
Keywords: Outer space -- Fiction